The Effect of Coffee Consumption on the Performance of the Human Digestive System: A Literature Study - Nasution, Rizki Khairani (UIN Syekh Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Coffee is one of the most widely consumed beverages worldwide and contains various bioactive compounds, such as caffeine, chlorogenic acid, and polyphenols, which have the potential to affect the human digestive system. The increasing pattern of coffee consumption, especially in modern society, raises questions about its impact on digestive system performance. This article aims to analyze the effect of coffee consumption on human digestive system performance based on a review of various relevant scientific findings. This study uses a qualitative approach with a literature review method to examine the relationship between coffee consumption levels and human digestive system performance. The discussion focuses on the effects of coffee on gastric acid secretion, gastrointestinal motility, digestive enzyme activity, and physiological responses of the gastrointestinal tract. The results of the study indicate that coffee consumption in certain amounts can have a stimulating effect on the digestive system, such as increased intestinal motility and gastric secretion. However, excessive coffee consumption has the potential to cause digestive disorders, including gastric irritation and gastrointestinal discomfort. Therefore, the level of coffee consumption is an important factor in determining its effects on digestive system performance. The conclusion of this article emphasizes that coffee consumption should be done moderately to obtain its physiological benefits without causing negative impacts on the human digestive system.